2017
DOI: 10.7717/peerj.2894
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+dynamics in zebrafish morphogenesis

Abstract: Intracellular calcium ion (Ca2+) signaling is heavily involved in development, as illustrated by the use of a number of Ca2+ indicators. However, continuous Ca2+ patterns during morphogenesis have not yet been studied using fluorescence resonance energy transfer to track the Ca2+ sensor. In the present study, we monitored Ca2+ levels during zebrafish morphogenesis and differentiation with yellow cameleon, YC2.12. Our results show not only clear changes in Ca2+ levels but also continuous Ca2+ patterns at 24 hpf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These indicators are based on modifications of calmodulin (CaM), in which the calciumbinding domain is fused to GFP. GCaMP indicators with different calcium sensitivities have been developed (GCaMP1, GcaMP3, GcaMP6, GcaMP6f, GcaMP6s, and GcaMP7) to check the cytoplasmic levels of calcium [147,149,150]. Modified GCaMP6f, which harbors a mitochondrial-specific leader peptide at the N-terminus, was developed to check calcium levels in mitochondria [151].…”
Section: Calcium Homeostasis and Oxidative Stress (Use Of Fluorescent...mentioning
confidence: 99%
“…These indicators are based on modifications of calmodulin (CaM), in which the calciumbinding domain is fused to GFP. GCaMP indicators with different calcium sensitivities have been developed (GCaMP1, GcaMP3, GcaMP6, GcaMP6f, GcaMP6s, and GcaMP7) to check the cytoplasmic levels of calcium [147,149,150]. Modified GCaMP6f, which harbors a mitochondrial-specific leader peptide at the N-terminus, was developed to check calcium levels in mitochondria [151].…”
Section: Calcium Homeostasis and Oxidative Stress (Use Of Fluorescent...mentioning
confidence: 99%
“…Intracellular calcium ions (Ca 2+ ) is very important in morphogenesis (Niki et al, 1996;Berridge, Lipp & Bootman, 2000;Slusarski & Pelegri, 2007). To date, consecutive Ca 2+ dynamics of zebrafish normal development was reported with fluorescent yellow cameleon YC2.12 (Tsuruwaka et al, 2007(Tsuruwaka et al, & 2016. We also reported that morphological changes brought about dramatic transition in Ca 2+ signaling (Tsuruwaka, Konishi & Shimada, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Intracellular calcium ions (Ca 2+ ) is very important in morphogenesis (Niki et al, 1996; Berridge, (Tsuruwaka et al, 2007(Tsuruwaka et al, & 2016. We also reported that morphological changes brought about 35 dramatic transition in Ca 2+ signaling (Tsuruwaka, Konishi & Shimada, 2015 …”
mentioning
confidence: 97%